The science of false memory - Brainerd, Charles J. (Oxford psychology series, 2005)
Four main topics comprise the core of false memory research : theories of false memory; adult experimental psychology of false memory; false memory in legal contexts; false memory in psychotherapy. This book integrates these different strands to offer a comprehensive overview of human false memory.